1999
DOI: 10.1046/j.1365-2133.1999.02986.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoid proteinosis. A biochemical and ultrastructural investigation of two new cases

Abstract: Lipoid proteinosis is a rare autosomal recessive disease characterized by cutaneous and visceral lesions, in which large amounts of amorphous material are constantly found in stroma. Morphological and biochemical studies indicate abnormal collagen production, but little attention has been paid to the lipid component of lesions. Microscopic and ultrastructural studies of skin, with special emphasis on fibroblasts, vessels, nerve endings and eccrine sweat glands, were conducted in two patients with lipoid protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 23 publications
0
34
0
3
Order By: Relevance
“…Vascular endothelial cells display high transcytotic activity [29,30]; in our LP-specimens frequently a dense lining of presumably discharging vesicles along membranes of endothelial cells and pericytes were associated with accumulating BM-material (type IV collagen positive by ImEM). Accordingly, storage defects (lipids) in LP-fibroblasts [31] may represent another manifestation of a default in intracellular transport [32]. Abundant vesicles could also mirror enforced secretion of excessive BM-molecules, occasionally accumulating in larger vacuoles (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial cells display high transcytotic activity [29,30]; in our LP-specimens frequently a dense lining of presumably discharging vesicles along membranes of endothelial cells and pericytes were associated with accumulating BM-material (type IV collagen positive by ImEM). Accordingly, storage defects (lipids) in LP-fibroblasts [31] may represent another manifestation of a default in intracellular transport [32]. Abundant vesicles could also mirror enforced secretion of excessive BM-molecules, occasionally accumulating in larger vacuoles (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy has disclosed small, disorganized collagen bundles and large amounts of non-filamentous substances in the dermis, with granular inclusions in lysosomes of eccrine glands, similar to those found in Farber disease [10]. Also reported are reduplications of basement membranes around capillaries, although the mechanisms underlying such changes remain a mystery [10][11][12][13]. Recently, molecular studies have identified mutations in the gene encoding the glycoprotein, extracellular matrix protein 1 (ECM1) [8,[14][15][16].…”
Section: Introductionmentioning
confidence: 95%
“…Immunohistochemistry reveals increased presence of type IV collagen within the hyaline-like substance, which is also present around dermal blood vessels [9]. Electron microscopy has disclosed small, disorganized collagen bundles and large amounts of non-filamentous substances in the dermis, with granular inclusions in lysosomes of eccrine glands, similar to those found in Farber disease [10]. Also reported are reduplications of basement membranes around capillaries, although the mechanisms underlying such changes remain a mystery [10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…Authors have reported mutation of the extracellular matrix protein 1 (EMP1) gene 3 ; profound alterations of EMP1 confirmed by molecular methods 4 ; and disturbances of collagen metabolism confirmed by biochemical, immunological, and ultrastructural methods. 5 Systemic involvement includes skin and mucosa of the larynx and pharynx. Other features are epilepsy and neuropsychiatric manifestations, intestinal bleeding, and lung and bronchial involvement.…”
Section: Discussionmentioning
confidence: 99%